CCN Family Proteins in Cancer: Insight Into Their Structures and Coordination Role in Tumor Microenvironment - Jia, Qingan; Xu, Binghui; Zhang, Yaoyao; Ali, Arshad; Liao, Xia (Frontiers in Genetics, 2021)
The crosstalk between tumor cells and the tumor microenvironment (TME), triggers a variety of critical signaling pathways and promotes the malignant progression of cancer. The success rate of cancer therapy through targeting single molecule of this crosstalk may be extremely low, whereas co-targeting multiple components could be complicated design and more likely to have more side effects. The six members of cellular communication network (CCN) family proteins are scaffolding proteins that may govern the TME, and several studies have shown targeted therapy of CCN family proteins may be effective for the treatment of cancer. CCN protein family share similar structures, and they mutually reinforce and neutralize each other and serve various roles that are tightly regulated in a spatiotemporal manner by the TME. Here, we review the current knowledge on the structures and roles of CCN proteins in different types of cancer. We also analyze CCN mRNA expression, and reasons for its diverse relationship to prognosis in different cancer. In this review, we conclude that the discrepant functions of CCN proteins in different types of cancer are attributed to diverse TME and CCN truncated isoforms, and speculate that targeting CCN proteins to rebalance the TME could be a potent anti-cancer strategy.